KINERJA UNIT DALAM MENDUKUNG PENGEMBANGAN FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING - nielwaty, elly; prihati, prihati; zuhdi, sulaiman (Jurnal Niara, 2018)
Performance Faculty of Administrative Sciences can be seen from the performance of employees. This study focuses on the performance of existing units in the Faculty of Administration in carrying out its main duties and functions in order to support the strengthening of Faculty's performance. But in reality the performance of existing units in the faculty of administration of the University of Lancang Kuning showed less satisfactory work. Indicators that are visible include unstructured unit work programs, inadequate facilities and infrastructure, limited budget support and weak leadership which are a constraint in motivating employees to do their job well. The objective of the study was to explain the performance of faculty units and their inhibiting factors. The research method uses qualitative with emphasis on the concept of performance measurement. The techniques used in data collection are observation, interview and documentation study. The results showed that the performance of the faculty unit has not run well, this is obtained from the measurement of performance indicators that include job performance, expertise, behavior and leadership. As for the inhibiting factors of faculty unit performance is the limited support of facilities, infrastructure and funding. Besides, the reward and punishment system has not been done to the employee job resulting in the employee's motivation in working to be reduced, besides it is necessary to be given guidance and training for the work unit to understand the duty and function properly.